Diabetic kidney disease: update on clinical management and non-glycaemic effects of newer medications for type 2 diabetes. (May 2021) - de Bhailís, Áine M.; Azmi, Shazli; Kalra, Philip A.
Type 2 diabetes is a leading cause of chronic kidney disease worldwide and continues to increase in prevalence. This in turn has significant implications for healthcare provision and the economy. In recent years there have been multiple advances in the glucose-lowering agents available for the treatment of diabetes, which not only modify the disease itself but also have important benefits in terms of the associated cardiovascular outcomes. The cardiovascular outcome trials of agents such as glucagon-like peptide-1 receptor agonists (GLP-RAs) and sodium glucose cotransporter 2 inhibitors (SGLT-2) have demonstrated significant benefits in reducing major adverse cardiovascular events, admissions for heart failure and in some cases mortality. Secondary analysis of these trials has also indicated significant renoprotective benefit. Canagliflozin and Renal Outcomes in Type 2 Diabetes Mellitus and Nephropathy (CREDENCE) a renal-specific trial, has shown major benefits with canagliflozin for renal outcomes in diabetic kidney disease, and similar trials with other SGLT-2 inhibitors are either underway or awaiting analysis. In this article we review current goals of treatment of diabetes and the implications of advancing renal impairment on choice of treatments. Areas discussed include the diagnosis of diabetic kidney disease and current treatment strategies for diabetic kidney disease ranging from lifestyle modifications to glycaemic control. This review focuses on the role of GLP-RAs and SGLT-2 inhibitors in treating those with diabetes and chronic kidney disease with some illustrative cases. It is clear that these agents should now be considered first choice in combination with metformin in those with diabetes and increased cardiovascular risk and/or reduced renal function, and in preference to other classes such as dipeptidyl peptidase-4 (DPP-4) inhibitors or sulphonylureas.